Health Related Quality of Life in Japanese Patients with Localized Prostate Cancer: Comparative Retrospective Study of Robot-Assisted Laparoscopic Radical Prostatectomy Versus Radiation Therapy - Miyoshi, Yoko (Yonago Acta Med, 2020)
BACKGROUND: Radical prostatectomy and radiotherapy are standard treatments for localized prostate cancer. When making decisions about treatment, it is important to not only consider medical information such as the patient’s age, performance status, and complications, but also the impact on quality of life (QOL) after treatment. Our purpose was to compare health related quality of life (HRQOL) after robot-assisted laparoscopic radical prostatectomy (RARP) versus radiation therapy in Japanese patients with localized prostate cancer retrospectively. METHODS: Patients with localized prostate cancer receiving RARP or radiotherapy at Tottori University Hospital between October 2010 and December 2014 were enrolled in a retrospective observational study with follow-up for 24 months to December 2016. The Medical Outcome Study 8-Item Short-Form Health Survey was performed before treatment and 1, 3, 6, 12, and 24 months post-treatment. RESULTS: Complete responses to the questionnaire were obtained from 154/227 patients receiving RARP, 41/67 patients receiving intensity-modulated radiation therapy, 35/82 patients receiving low dose rate brachytherapy, and 18/28 patients given low dose rate brachytherapy plus external beam radiation therapy. The median physical component summary score of the Medical Outcome Study 8-Item Short-Form Health Survey was significantly lower at 1 month after prostatectomy than radiotherapy, but was similar for both treatments at 3 months, and was significantly higher at 6, 12 and 24 months after prostatectomy. The median mental component summary score was also significantly lower in the prostatectomy group at 1 month, but not from 3 months onwards. CONCLUSION: Our study suggested that HRQOL was inferior at 1 month after RARP, however, recovered at 3 months after RARP and was better than after radiotherapy at 6, 12, and 24 months.